Properties of therapeutic deep eutectic solvents of L-arginine and ethambutol for tuberculosis treatment - Santos, Filipa (2020)
The treatment for tuberculosis infection usually involves a prolonged regimen of multiple antibacterial drugs, which might lead to various secondary effects. For preventing drug resistance and side-effects of anti-tuberculosis drugs, new methods for improving the bioavailability of APIs were investigated. The strategy proposed consists of the preparation of therapeutic deep eutectic solvents (THEDES), that incorporate L-arginine and ethambutol. The eutectic mixtures were prepared by mixing the components at a certain molar ratio, until a clear liquid solution was formed. The prepared mixtures were characterized by differential scanning calorimetry (DSC), polarized optical microscopy (POM) and nuclear magnetic resonance spectroscopy (1H and 13C-NMR). The solubility and permeability of the drugs when they are in the THEDES form was evaluated at 37 °C, in phosphate buffered saline (PBS). Solubility studies showed an increase of the solubility of ethambutol when incorporated in the eutectic system. The cytotoxicity was evaluated using a model cell line (Caco-2), comparing the cytotoxicity of the API incorporated in the eutectic system. We observed that the cell viability in the THEDES was affected by the presence of citric acid, and higher cytotoxicity values were observed. Nonetheless, these findings do not compromise the possibility to use these systems as new delivery systems for ethambutol and arginine.